2014
DOI: 10.1021/mp500364a
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptide–Selenium Nanoparticles as Drug Transporters

Abstract: A cyclic peptide composed of five tryptophan, four arginine, and one cysteine [W5R4C] was synthesized. The peptide was evaluated for generating cyclic peptide-capped selenium nanoparticles (CP–SeNPs) in situ. A physical mixing of the cyclic peptide with SeO3–2 solution in water generated [W5R4C]–SeNPs via the combination of reducing and capping properties of amino acids in the peptide structure. Transmission electron microscopy (TEM) images showed that [W5R4C]–SeNPs were in the size range of 110–150 nm. Flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…The calculated E g and η of CPSeNP/GCB1‐15 are lower than those of CP and GCB drug, demonstrating the reactivity of CP and GCB increases for CPSeNP/GCB1‐15 systems in both phases. Since ω is utilized to predict toxicity, it may be concluded that the toxicity of SeNP is reduced in the presence of the GCB and CP . The ω values of CPSeNP/GCB1‐15 are higher than those of GCB in both phases, indicating that GCB is the electron acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated E g and η of CPSeNP/GCB1‐15 are lower than those of CP and GCB drug, demonstrating the reactivity of CP and GCB increases for CPSeNP/GCB1‐15 systems in both phases. Since ω is utilized to predict toxicity, it may be concluded that the toxicity of SeNP is reduced in the presence of the GCB and CP . The ω values of CPSeNP/GCB1‐15 are higher than those of GCB in both phases, indicating that GCB is the electron acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the linear CPPs, a number of synthetic cyclic polyarginines with efficient cell permeability have also been recently proposed as CPPs to assist the intracellular delivery of proteins, drugs and nucleic acids [ 12 , 14 , 46 , 47 , 48 , 49 , 50 ]. Our results show that these cyclic polyarginines also represent potent inhibitors of furin activity in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, research on direct conjugation of biocompatible agents and biomolecules to nanoparticles is accomplishable [38]. For example, SeNPs capped with biocompatible agents, such as lipid bilayers [39,40] and dendrimers [41], have been prepared with water solubility and potential biocompatibility. Biomolecules, such as amino acid, have also been used as protective agents for the formation of SeNPs.…”
Section: Introductionmentioning
confidence: 99%